The role of time and past funding in non-investment crowdfunding decision - Barros, Lucia Salmonson Guimarães (2017)
Although there has been growing interest in how solicitors and funders behave in crowdfunding platforms, it is an open question whether and if so how information about the time left to complete the campaign and past funding impact funder’s decision in all-or-nothing non-investment crowdfunding platforms. Relying on a new outcome measure: the funding rate (i.e., the ratio of the number of supports to number of web page visits on a given week), and a unique dataset of about three and a half million web page visits and 79.6 thousand supports for 931 different projects, this research investigates the impact of past funding and time on a project’s funding rate in the largest 'all or nothing' non-investment Brazilian crowdfunding platform. We found that people seem concerned about the usefulness of their funds: they are willing to help solicitors, but mainly when they believe the project is good (i.e., it has a minimum chance of reaching the target) and when 'their help really helps' (i.e., before the target is reached).